More than Just Friends? School Peers and Adult Interracial Relationships - Luca Paolo Merlino; Max F. Steinhardt; Liam Wren-Lewis (Institute for the Study of Labor (IZA), 2016)
This paper investigates the impact of individuals' school peers on their adult romantic relationships. In particular, we consider the effect of quasi-random variation in the share of black students within an individual's cohort on the percentage of adults' cohabiting partners that are black. We find that more black peers leads to more relationships with blacks later in life. The results are similar whether relationships begun near or far from school, suggesting that the racial mix of schools has an important and persistent impact on racial attitudes.
Keywords: J12; J15; J16; 330; assortative matching; romantic relationships; race